Is it really necessary to perform venous anastomosis in vascularized corticoperiosteal bone flap? A randomized prospective 4-year follow-up study. Issue 8 (August 2022) - Guzzini, Matteo; Arioli, Leopoldo; Mori, Fabiana; Ferretti, Andrea
Abstract: Background: This study aims to investigate the treatment results of atrophic nonunion of the lower and upper limb with vascularized bone flaps performed with only arterial anastomosis versus the execution of flaps performed with arterial and venous anastomosis, comparing the surgical time and the healing rate of these two techniques. Methods: 49 patients were enrolled in this study and were randomly divided into two groups: group A, the control group, consisted of 27 patients, who underwent vascularized corticoperiosteal bone flap with both arterial and venous anastomosis; group B, consisted of 22 patients, who underwent vascularized corticoperiosteal bone flap with only arterial anastomosis. The surgical time, the time to harvest the graft and the microsurgical time were evaluated. Radiological and clinical follow-ups were performed with one independent and blinded investigator to avoid bias. Results: A significant reduction in the duration of the intervention in group B was found: a 13.63% reduction of the total surgical time and a 41.75% reduction of the microsurgical time. A significant difference was not found between groups A and B in bone healing time. All the patients of both groups were able to return to their daily life activities. Conclusions: Our investigation suggests that it isn't necessary to perform the venous anastomosis between the flap pedicle and the recipient area. Presumably, the venous blood flow reaches the systemic circulation through the vascular bone marrow network. Our procedure avoids venous trauma during the dissection and execution of the anastomosis and, therefore, can minimize complications such as venous thrombosis.